Boosting Employee Performance through Discipline, Motivation, and Supervision in Indonesia: Meningkatkan Kinerja Karyawan melalui Disiplin, Motivasi, dan Pengawasan di Indonesia - Setianto, Jey Devan; Firdaus, Vera (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the influence of discipline, motivation, and supervision on employee performance at Toby's branches in Sidoarjo. Conducted with a sample of 60 employees, data were collected via questionnaires, direct observations, and interviews. Using SPSS for data analysis, the results revealed that discipline, motivation, and supervision each have a positive and significant impact on employee performance. Additionally, the combined effect of these variables is also significant. The findings suggest that focusing on improving discipline, motivation, and supervision can enhance employee performance in retail settings like Toby's. Highlight: Analyzed discipline, motivation, and supervision's impact on employee performance. Data from 60 employees via questionnaires, observations, and interviews. All variables significantly improved employee performance. Keyword: Discipline, Motivation, Supervision, Employee Performance, Retail Industry